2020
DOI: 10.11604/pamj.2020.36.180.20765
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of onchocerciasis after seven years of continuous community-directed treatment with ivermectin in the Ntui health district, Centre region, Cameroon

Abstract: Introduction onchocerciasis is one of the major infectious diseases caused by Onchocerca volvulus. This parasite is responsible for chronic cutaneous and ocular diseases affecting more than 37 million people of whom 99% are in Africa. The study was conducted in the health district of Ntui from June to September 2016 to determine the prevalence of O. volvulus infection after seven years of massive administration of ivermectin. Methods two cutaneous snips were made at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Over 60% of individuals live in high-risk areas, 2.8 million people are infected, and 5.2 million people are in danger of infection [ 6 ]. A prevalence of 10.7% and 6.7% in men and women, respectively, was recorded after seven years of continuous community-directed treatment of skin conditions with ivermectin in the central region [ 7 ]. A study carried out in southern Cameroon showed that out of 9,456 subjects diagnosed, the prevalence of onchocerciasis was 44.4% [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over 60% of individuals live in high-risk areas, 2.8 million people are infected, and 5.2 million people are in danger of infection [ 6 ]. A prevalence of 10.7% and 6.7% in men and women, respectively, was recorded after seven years of continuous community-directed treatment of skin conditions with ivermectin in the central region [ 7 ]. A study carried out in southern Cameroon showed that out of 9,456 subjects diagnosed, the prevalence of onchocerciasis was 44.4% [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…To face onchocerciasis, the control methods based on the treatment by eliminating the worms in the patients and disease prevention by the reduction of the vector bites are employed [ 9 ]. As the anti-vector control was given up, chemotherapy remains the main control method to combat onchocerciasis.…”
Section: Introductionmentioning
confidence: 99%
“…It is one of eleven NTDs that the World Health Organization (WHO) has recently targeted for eradication. 5,6 The WHO reports that 198 million people are at risk of contracting onchocerciasis, but this number could rise as the mapping of low-transmission areas is completed. 7 In 2013, the global burden of disease (GBD) report reported that 17 million people were infected worldwide.…”
Section: Introductionmentioning
confidence: 99%